Facile synthesis of nitrogen doped reduced graphene oxide as a superior metal-free catalyst for oxidation - Sun, Hongqi; Wang, Y.; Liu, S.; Ge, L.; Wang, L.; Zhu, Z.; Wang, Shaobin (2013)
Nitrogen (5.61 at%) doped reduced graphene oxide synthesized via a facile method was demonstrated as a superior metal-free catalyst for activation of peroxymonosulfate. Codoping with boron would further enhance the catalytic activity and the stability, providing a promising green material for environmental remediation.